Assessment of P2Y12 Inhibition by Clopidogrel in Feline Platelets Using Flow Cytometry Quantification of Vasodilator-Stimulated Phosphoprotein Phosphorylation - Li, Ronald H. L.; Nguyen, Nghi; Rosati, Tommaso; Jandrey, Karl (Frontiers in Veterinary Science, 2020)
The primary objective of this study was to evaluate a novel flow cytometry-based assay of quantifying platelet phosphorylation ofvasodilator-stimulated phosphoprotein (P-VASP) in cats that received clopidogrel treatment. Eight healthy cats received 18.75 mg PO q24h of clopidogrel for 7 days. Prior to and after clopidogrel treatment, blood was collected for ADP-induced light transmission aggregometry (LTA) and P-VASP measurement by flow cytometry. Flow cytometry measurement of P-VASP levels was used to derive platelet reactivity index (PRI) before and after clopidogrel treatment. Based on P-VASP and LTA findings, platelet response to ADP was significantly attenuated after 7 days of clopidogrel treatment. By eliciting the competing platelet pathways of P2Y12 and cAMP using ADP and PGE1, respectively, ADP had no effect on P-VASP levels following clopidogrel treatment (p=0.94). Clopidogrel also significantly decreased PRI (Day 0: 28.84% ±28.52, Day 8: 1.69% ± 12.39) (p=0.0078). PRI on day 8 correlated moderately with the degree of slope inhibition on LTA (r=-0.4, p=0.4). Flow cytometry analysis of P-VASP is effective at monitoring the inhibitory effects of clopidogrel on feline platelets.